2020
DOI: 10.1371/journal.pone.0233317
|View full text |Cite
|
Sign up to set email alerts
|

The SAPS 3 score as a predictor of hospital mortality in a South African tertiary intensive care unit: A prospective cohort study.

Abstract: Background No African countries were included in the development of the Simplified Acute Physiology Score 3 (SAPS 3). This study aimed to assess the performance of the SAPS 3 as a predictor of hospital mortality in patients admitted to a multidisciplinary tertiary intensive care unit (ICU) in South Africa. Methods A prospective cohort study was undertaken in a tertiary single-centre closed multidisciplinary ICU with 16 beds over 12 months in 2017. First time admissions 12 years and over were included. Exclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The SAPS 3 is a well-validated scoring system widely used around the world for the prediction of hospital mortality. 21 , 22 However, a recent study investigated the performance of the SAPS 3 score in 30.571 patients admitted to private ICUs in Brazil. The authors investigated if adjustments in the SAPS 3 score modifies its performance and suggested that SAPS 3 should be used with caution for mortality prognosis in critically ill patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The SAPS 3 is a well-validated scoring system widely used around the world for the prediction of hospital mortality. 21 , 22 However, a recent study investigated the performance of the SAPS 3 score in 30.571 patients admitted to private ICUs in Brazil. The authors investigated if adjustments in the SAPS 3 score modifies its performance and suggested that SAPS 3 should be used with caution for mortality prognosis in critically ill patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…[9,28,29] The ICU and hospital mortality of 31.1% and 42.9%, respectively, in our long-stay cohort are also high taking into account that the overall 2017 ICU and hospital mortality in the same unit and hospital for all ICU admissions were 13.3% and 21.4%, respectively. [17] It is worth noting that 21.2% of the deaths occurred while in hospital post ICU discharge, and a further 18.2% occurred within 6 months after hospital discharge. This finding points towards the fact that long-stay patients warrant some form of monitoring after discharge from the ICU for setbacks, both in the hospital and on an outpatient basis.…”
Section: Discussionmentioning
confidence: 97%
“…In SA, ICU admissions tend to be younger, HIV-positive rates are high, and there is a RESEARCH preponderance of surgical emergency and trauma admissions. [17][18][19] These variations and the large proportion of the ICU budget that is spent on long-stay ICU survivors necessitate that we ascertain survival and the HRQOL in the SA setting.…”
Section: Researchmentioning
confidence: 99%
“…In the current SAJCC issue, Pazi et al, [12] using a cohort of 829 patients admitted to an adult ICU in a tertiary hospital in South Africa (SA), have developed a SAPS III-based mortality prediction model calibrated to their specific ICU population using data available from a previous SAPS III validation study. [13] Data were collected for one year starting in January 2017. They reported a mortality rate of 21.35%.…”
Section: Editorialmentioning
confidence: 99%